Le climat est-il une ressource ? Perspectives historiques à partir de la conception bioclimatique en architecture - Clément Gaillard (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
From the development of a bioclimatic architectural approach, this article aims to study under which conditions the climate can be considered a resource. Based on the study of archives and interviews with architects and engineers, it shows the way in which this method of design has historically been structured from the idea that the climate gathers a set of potentially useful energy resources. Following this historical analysis, the article focuses on the case of "solar deposits" and the difficulties of capturing this resource. In our view, these difficulties, as well as problems of equality in terms of access to favorable climate inputs, reflect the equivocal nature of the climate as a resource, which we believe is relevant today.